2009
DOI: 10.1530/eje-09-0063
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oral and transdermal estrogen therapies on circulating cytokines and chemokines in postmenopausal women with hysterectomy

Abstract: Objective: The aim of the present study was to determine the different effects of oral estrogen therapy (ET) and transdermal ET on changes in circulating levels of cytokines and chemokines in relationship to changes in markers of inflammation in postmenopausal women with hysterectomy. Methods: Fifty-five postmenopausal women with hysterectomy were randomly assigned in open, parallel-group fashion to an oral ET group and a transdermal ET group. Serum levels of cytokines and chemokines were simultaneously measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 36 publications
0
13
0
1
Order By: Relevance
“…Although the identity of the RANKL-expressing cells in this latter study was not determined, the cells were in the flowcytometric fraction that contains lymphocytes. Consistent with the idea that B cells may increase in estrogen-deficient women, administration of estradiol or raloxifene to post-menopausal women reduces circulating levels of IL-7 (44,45).…”
Section: Discussionmentioning
confidence: 56%
“…Although the identity of the RANKL-expressing cells in this latter study was not determined, the cells were in the flowcytometric fraction that contains lymphocytes. Consistent with the idea that B cells may increase in estrogen-deficient women, administration of estradiol or raloxifene to post-menopausal women reduces circulating levels of IL-7 (44,45).…”
Section: Discussionmentioning
confidence: 56%
“…Estrogen, specifically E2, is secreted mainly by the ovaries in premenopausal women (Shimizu, 2010). Estrogen circulates in the bloodstream and affects many tissues, including the urogenital system (Yasui et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This may be related to the regulatory effects of estrogen on the production of inflammatory cytokines (Georgiadou & Sbarouni 2009). For instance, an in vivo study showed that transdermal estrogen therapy reduces circulating levels of several cytokines, including MCP-1 (Yasui et al 2009). In parallel, studies in vitro demonstrate that estrogen reduces MCP-1 production in several cells, such as peripheral blood mononuclear cells and immature dendritic cells (Bengtsson et al 2004, Yuan et al 2008).…”
Section: Discussionmentioning
confidence: 99%